The Effect of Gender and Teaching Methods on Academic Success in Virtual Reality to Reduce Gender Disparity in Technology - Onele, Nicholas Ogbonna; Ogbuanya, Theresa Chinyere (Journal of Teaching and Learning)

(untitled) (University of Windsor, 2025)
This study adopted a pre-test post-test quasi-experimental design. The sample size was 162 students from eight universities. The sample was categorized into two groups: Group I (n=79) and Group II (n=83). Electric VLab, provided the environment. A researcher-made achievement test, comprising multiple-choice, essay and practical questions was used for assessment and data collection. Two weeks before the treatment, students in both groups were given a pre-test in electronics circuit construction and assembly. Before the treatment, one week was used to train the groups on how to use the Electric VLab. During the treatment, each intact class in Group I was taught using the direct instruction method, and the other classes in Group II were divided into units of five students with a selected peer tutor leading each unit while the teacher coordinated the learning. At the end of treatment, the post-test was administered to both groups. Mean statistics, standard deviation, and analysis of covariance were used to analyze the data. There was no significant difference between the achievement of male students in both groups. Female students in indirect instruction classes achieved significantly higher than their counterparts in direct instruction classes. There were significant effects of interaction between teaching methods and gender.